Optimalisasi Keuangan Usaha Mikro, Kecil, dan Menengah (UMKM) Batok Atha Craft dengan Aplikasi Financial Digital - Ahmada Rifqi Zulfahmi; Niniek Imaningsih; Cholid Fadil (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
This article aims to elaborate the use of digital financial applications to micro, small, and medium enterprises (MSMEs) in Gedog village, Blitar City. Financial optimization of micro, small, and medium enterprises (MSMEs) Batok Atha Craft uses a digital financial application called BukuWarung. This effort is carried out in order for business owners to be able to separate their business assets and personal assets, make the financial books of MSMEs systemized, and make it easier to evaluate financial performance. The average obstacle experienced by business owners is the inability to make good financial reports so that it is difficult to detect business financial performance. Therefore, this service activity is a pragmatic effort in breaking a series of obstacles faced by MSMEs in Gedog village, Blitar city